การพัฒนาเส้นทางท่องเที่ยวเชิงวัฒนธรรมริมแม่น้ำปากพนังเพื่อส่งเสริมการตลาดท่องเที่ยว อำเภอปากพนัง จังหวัดนครศรีธรรมราช - ช่วยแก้ว, ธนาภา; จิโรจน์กุล, สุดใจ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2019.48, 2019)
การศึกษานี้มีวัตถุประสงค์ 1) เพื่อสำรวจแหล่งท่องเที่ยวเชิงวัฒนธรรมนำมากำหนดเส้นทางท่องเที่ยวเชิงวัฒนธรรมริมแม่น้ำปากพนัง 2) เพื่อพัฒนาองค์ประกอบด้านการท่องเที่ยวเชิงวัฒนธรรมริมแม่น้ำปากพนังใน 3 ด้าน คือ ด้านแหล่งท่องเที่ยว ด้านบริการทางการท่องเที่ยว และด้านตลาดทางการท่องเที่ยว 3) จัดทำและนำเสนอเส้นทางท่องเที่ยวเชิงวัฒนธรรมริมแม่น้ำปากพนัง โดยผู้วิจัยได้ศึกษาและรวบรวมข้อมูลทุติยภูมิจากเอกสาร งานวิจัย และข้อมูลปฐมภูมิได้จากการสำรวจพื้นที่เพื่อประเมินศักยภาพเส้นทางเบื้องต้น การสนทนากลุ่มเพื่อกำหนดเส้นทางท่องเที่ยวเชิงวัฒนธรรมริมแม่น้ำปากพนัง การทดสอบเส้นทางท่องเที่ยวเพื่อประเมินความพึงพอใจของผู้มีส่วนเกี่ยวข้อง นำข้อเสนอแนะมาแก้ไข ปรับปรุง และพร้อมมอบให้ชาวบ้านและหน่วยงานในพื้นที่นำไปใช้ส่งเสริมด้านการตลาดท่องเที่ยวต่อไป การวิจัยเชิงปฏิบัติการนี้ผลการศึกษา พบว่า ริมแม่น้ำปากพนังมีมรดกทางวัฒนธรรมที่หลากหลาย ประกอบด้วยวิถีชีวิตชาวประมงพื้นบ้านเกาะไชย ภูมิปัญญาการทำขนมลาของบ้านหอยราก โรงสีแม่ครูที่เป็นร่องรอยบ่งบอกถึงความอุดมสมบูรณ์ของพื้นที่ผลิตข้าวที่สำคัญของภาคใต้ในอดีต ความศรัทธาต่อหลวงพ่อผุดวัดนันทาราม อุโบสถไม้โบราณวัดรามประดิษฐ์ บ้านพักเชิงนิเวศบ้านวงศ์เบี้ยสัจจ์ และพระตำหนักประทับแรมของในหลวงรัชกาลที่ 9 ซึ่งเป็นแหล่งท่องเที่ยวที่มีศักยภาพที่จะสามารถนำมากำหนดเป็นเส้นทางท่องเที่ยวเชิงวัฒนธรรมริมแม่น้ำปากพนังแบบเต็มวันหรือ Full Day Tour Itinerary อันจะช่วยส่งเสริมด้านการตลาดท่องเที่ยวตามแนวคิด “วันเดียวเที่ยวปากพนัง” ภายใต้ชื่อรายการนำเที่ยว “ล่องเรือหา...รักษ์ ที่ปากพนัง” โปรแกรมท่องเที่ยวสามารถดึงดูดนักท่องเที่ยวได้ตามหลักการส่วนประสมทางการตลาดแบบ 4 P’s ส่งเสริมสินค้าทางการท่องเที่ยวให้เข้าถึงผู้บริโภคได้มากที่สุด คำสำคัญ: การท่องเที่ยวเชิงวัฒนธรรม, ริมแม่น้ำปากพนัง, การส่งเสริมการตลาดท่องเที่ยว   The objectives of this study aimed 1) to survey the cultural heritage and way of life of the villagers along Pak Phanang River, in order to plan cultural tourism route along the river, 2) to develop cultural tourism route in 3 aspects; tourist attraction, tourism services, and tourism marketing promotion., 3) to prepare, present, and publicize cultural tourism route along the Pak Phanang River by using marketing mix for tourism promotion commercially. The researcher studied and collected relevant secondary data from research papers, related academic texts, and primary data were obtained from the survey trip, group discussion, and tourist satisfaction evaluation for pilot tour itinerary. Adjusted, improved, and gave the ready-made itinerary to the villagers and local community to use for tourism marketing promotion. The methodology of this research was an action research. The study found that the Pak Phanang River has a rich and diversity of cultural heritage; including of the traditional way of life of the local fishermen at Koh Chai Community, the faith and belief of Thai people for Luang Po Phud at Nantaram Temple, an ancient wooden chapel at Ram Pradit Temple, eco house at Baan Wong Bia Sajj, the ruins of rice mill factory at Rong Si Mae Kru, which indicates how important rice production areas in the southern region in the past, the King Rama 9’s Royal House was built with the loyalty of the people in Nakhon Si Thammarat Province, and the local wisdom of making of Khnom La Baan Hoy Rak. All can be defined as a cultural tourism route along the Pak Phanang River by setting up a full day tour program (Itinerary) by long-tail boat under the name of “Pak Phanang Full Day Trip: Cruise for.. Conserved at Pak Phanang” that can attract tourists by using Marketing Mix (4P’s) Keywords: cultural tourism, Pak Phanang River, tourism marketing promotion